Case report of a large lipoma discovered intraoperatively in a chronically irritated implantable cardioverter-defibrillator pocket. Issue 7 (21st June 2022) - Burger, Heiko; Göbel, Gerhard; Richter, Manfred; Pecha, Simon
Abstract: Background: The implantation of cardiac implantable electronic devices is a globally established therapy to treat cardiac arrhythmias with low complication rates. Apart from technical problems, however, complications can arise from the implanted material. This can lead to bleeding, infections, or chronic irritation of the generator pocket, resulting in swellings, seromas, perforations, or fistulas. However, the cause of tissue changes is not always clear, and therefore, we would like to report on a rare tissue degeneration diagnosed in a patient. Case summary: After a history of ventricular fibrillation, a 46-year-old patient received an implantable cardioverter-defibrillator (ICD) for secondary prevention. Six years later, the generator pocket swelled without evidence of infection. With the suspected diagnosis of a chronically irritated pocket, the device was then surgically relocated. After a 2-year symptom-free period, the patient presented again with a severely swollen but only slightly painful device pocket. Once again, there were no signs of infection, and so the pocket was revised again, assuming a chronic irritant effusion. Intraoperatively, a lipomatous structure (12 × 6 × 3 cm) emerged from the subpectoral ICD pocket. After its complete removal, the histopathological examination revealed a lipoma. A bacterial genesis could be ruled out by microbiological samples, and the wound healed cosmetically well and without further discomfort. Conclusion: This case shows that the reason of chronically irritated generator pockets, in addition to the usually known tissue changes, can also be tumours. Therefore, resected tissue should be examined histopathologically and, if indicated, specific therapy initiated.